2019
DOI: 10.1101/2019.12.16.877365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pooled analysis of radiation hybrids identifies loci for growth and drug action in mammalian cells

Abstract: Genetic screens in mammalian cells commonly focus on loss-of-function approaches. To evaluate the phenotypic consequences of extra gene copies, we used bulk segregant analysis (BSA) of radiation hybrid (RH) cells. We constructed six pools of RH cells, each consisting of ∼2500 independent clones, and placed the pools under selection in media with or without paclitaxel. Low pass sequencing identified 859 growth loci, 38 paclitaxel loci, 62 interaction loci and 3 loci for mitochondrial abundance at genome-wide si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(183 reference statements)
1
0
0
Order By: Relevance
“…We have demonstrated that BSA is a powerful approach in determining genes related to drug resistance (this study) in P. falciparum , paralleling findings from other organisms 4750 . In other work we have used BSA to examine the impact of culture conditions (serum or AlbuMAX) 16 , and identifying genome regions that impact parasite fitness 15 .…”
Section: Discussionsupporting
confidence: 73%
“…We have demonstrated that BSA is a powerful approach in determining genes related to drug resistance (this study) in P. falciparum , paralleling findings from other organisms 4750 . In other work we have used BSA to examine the impact of culture conditions (serum or AlbuMAX) 16 , and identifying genome regions that impact parasite fitness 15 .…”
Section: Discussionsupporting
confidence: 73%